Scenario of Horticulture Research and Development in India and Northeastern India - Patel, V B; Tripathi, P C (Indian Horticulture, 2024)
The Northeast region has a vast scope of horticultural crops. The temperate crops have a lot of potential in the hilly regions, similarly, flower crops particularly orchids, Lilium, anthurium, etc. Research on the mushroom cultivation and processing of produce are other potential areas that need to be encouraged in the region. There is a need to promote product diversification in a unit of land through horticulture to increase the land capacity and bring the land to its full potential by linking to assured marketing channels through identifying demands and outlets of the products in Northeast India.